A qualitative study on the working experiences of clinical pharmacists in fighting against COVID-19 - Xiaojuan Wang; Xiali Yao; Xuedong Jia; Xiangfen Shi; Jie Hao; Yantao Yang; Gang Liu; Xiaojian Zhang; Shuzhang Du; Zhao Yin (BMC, 2022)
Abstract Background The spread of coronavirus disease 2019 (COVID-19) has overwhelmed healthcare systems across the world. Along with the medical team, clinical pharmacists played a significant role during the public health emergency of COVID-19. This study aimed to explore the working experience of clinical pharmacists and provide reference for first-line clinical pharmacists to prepare for fighting against COVID-19. Methods A qualitative study based on descriptive phenomenology was employed with face-to-face and audio-recorded interviews to study the working experience of 13 clinical pharmacists (including two clinical nutritional pharmacists). All interviews were transcribed verbatim, and the interview data were analyzed thematically using NVivo software. Results Four themes emerged from interview data, including roles of clinical pharmacists, working experiences of clinical pharmacists, psychological feelings of clinical pharmacists, and career expectations of clinical pharmacists. Conclusions The results contributed to a deeper understanding of the clinical pharmacists' work experiences in COVID-19 and offered guidance to better prepare clinical pharmacists in participating in a public health crisis.